Practical help for small-scale farmers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
A useful trio of new handbooks has just been issued in the Agrodoks series, published by CTA and Agromisa.